1975
DOI: 10.7589/0090-3558-11.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Rabies Neutralizing Antibodies in Wild Carnivores Following an Outbreak of Bovine Rabies

Abstract: In an outbreak of bovine rabies in Argentina, a study was made of vampire bats (Desmodus rotundus) and wild carnivores. Rabies antibody rates of high prevalence were found in the bats, foxes (Dusicyon gymnocercus) and skunks (Conepatus chinga). The outbreak was part of an extensive continuing epizootic of vampire transmitted bovine rabies which may have also involved other vectors in the area of this study. Consumption of dead and dying bats by the carnivores is the suggested means of passage of rabies virus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1983
1983
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…Samples of saliva, serum, salivary glands, brown fat, lung, and muscle of some live bats and all dead bats found inside or near roosts were sent to a laboratory for virological or serological testing (see [28,[34][35][36][37][38]). We also tested samples from other wild animals found sick or dead during outbreaks of vampire bat rabies [39].…”
Section: Rabies Samplesmentioning
confidence: 99%
“…Samples of saliva, serum, salivary glands, brown fat, lung, and muscle of some live bats and all dead bats found inside or near roosts were sent to a laboratory for virological or serological testing (see [28,[34][35][36][37][38]). We also tested samples from other wild animals found sick or dead during outbreaks of vampire bat rabies [39].…”
Section: Rabies Samplesmentioning
confidence: 99%
“…Mahan concluded there was no association between the rabies-bat association and rabies associations with carnivores. Lord et al (1975a) surveyed vampire bats and carnivores following an outbreak of rabies in cattle in Argentina. Antibody prevalence in cattle was 33% (n = 48), in vampire bats, 58% (n = 12), in foxes, Dusicyon gymnocercus, 50% (n = 8), and in skunks, Conepatus chinga, 100% (n = 2).…”
Section: Rabies Infoxes In the United Statesmentioning
confidence: 99%
“…Experimental inoculations of foxes (Kovalev et al, 1971;, skunks (Bell and Moore, 1971;Ramsden and Johnston, 1975), predatory birds , and crows (see Section I, herein) have shown the susceptibility of nonmurine species to oral infection. Transmission of rabies through cannibalism and scavenging also has been reported (Winkler et al, 1972;Lord et al, 1975;Gething, 1976;Shah and Jaswal, 1976). Irvin (1970) suggested that transmission of rabies virus by means other than bite is of primary importance in maintaining the virus during the endemic sylvatic cycle of the disease.…”
Section: Introductionmentioning
confidence: 95%